2001
DOI: 10.1021/om010661k
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of 2,2‘-Bipyridyl and 1,10-Phenanthroline to Substituted Ytterbocenes:  An Experimental Investigation of Spin Coupling in Lanthanide Complexes

Abstract: Addition of 2,2‘-bipyridyl to diamagnetic (Me5C5)2Yb(OEt2) gives the brown adduct (Me5C5)2Yb(bipy). The solution 1H NMR and electronic absorption spectra show that the bipyridyl complex is paramagnetic, containing a bipyridyl radical anion, which can also be detected in the solid-state infrared spectrum and by the single-crystal X-ray crystallographic analysis. However, the measured magnetic moment, which varies from less than 1 μB at 5 K to 2.5 μB at 300 K, is higher than expected for (Me5C5)2YbII(bipy0) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
330
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(364 citation statements)
references
References 33 publications
32
330
2
Order By: Relevance
“…The 3,8-Me 2 phen adduct is somewhat more soluble in toluene, but all of the neutral adducts are much less soluble than the 2,2'-bipyridine adducts described in earlier papers. 4,5,14,28 The solid-state and solution-state physical properties of the adducts are quite different and these properties are described in the separate sections that follow. The neutral phen adduct may also be sublimed at 190 °C under reduced pressure to yield dark purple crystalline material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3,8-Me 2 phen adduct is somewhat more soluble in toluene, but all of the neutral adducts are much less soluble than the 2,2'-bipyridine adducts described in earlier papers. 4,5,14,28 The solid-state and solution-state physical properties of the adducts are quite different and these properties are described in the separate sections that follow. The neutral phen adduct may also be sublimed at 190 °C under reduced pressure to yield dark purple crystalline material.…”
Section: Resultsmentioning
confidence: 99%
“…14 The spectra are available in SI. Morris and co-workers have given a detailed analysis of the solution spectra from 400 nm to 2500 nm of [Cp* 2 Yb(phen)] 0,+ .…”
Section: Vis-nir Spectramentioning
confidence: 99%
“…In particular, Cp* 2 Yb(bipy), 3, where Cp* is pentamethylcyclopentadienyl and bipy is 2,2'-bipyridine, displays, as does 1, strong exchange coupling between a ligand-based radical and a trivalent Ln center. [14][15][16][17] Previous studies have shown that 3 is multiconfigurational. 15 16 Computational modeling showed that the multiconfigurational ground state is due to mixing of low-lying excited states into the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, the magnetic moments in these complexes are lower than expected, which implies that the spin carriers are coupled, that is, the spin on the [Cp' 2 Yb(III, 4f 13 )] fragment is coupled with the spin on the bipy-X radical anion (S= ½) fragment. Although the spin carriers are antiferromagnetically coupled, the mechanism by which they couple is not clear; the coupling mechanism is important since exchange coupling between f-electrons with paired electrons or with other f-electrons is generally weak.…”
Section: Introductionmentioning
confidence: 78%
“…The sigma donor orbitals on each nitrogen atom of bipy and dad(H)-R transform as a 1 +b 2 (in C 2v symmetry). The LUMO is of b 1 symmetry (in C 2v symmetry) in each case as illustrated in A and B. The energy of the LUMO is measured by the reduction potential of the neutral ligands.…”
Section: Comparison Between Bipy and Dad(r')-r Ligandsmentioning
confidence: 99%